O papel das empresas no impacto econômico da mulher no mercado de trabalho a partir da promoção da igualdade de gênero - Costa, Daiane Teixeira (2023)
Around the world, women are less paid than men and continue to be primarily responsible for household chores and family responsibilities. In addition, it is still possible to understand that millions of women still do not have the fundamental right to adequate maternity protection. These and other aspects of reality have led the world and its sectors to adopt policies, such as the 2030 Agenda, which address the root causes and consequences of gender inequality and discrimination in all areas of life, especially in the workplace. Overcoming challenges to gender equality compliance requires a comprehensive approach that eradicates unconscious bias, promotes gender-neutral hiring and career progression processes, manages resistance to change, and fosters a supportive organizational culture. By implementing these strategies, companies can create inclusive workplaces that value diversity, empower all employees, and contribute to the achievement of gender equality goals. In view of this, this study emerges as the objective of understanding the role of companies in the promotion of gender equality. For this, the Bibliographic and Documentary Review Methodology was adopted, in a deductive and exploratory method; coming to the conclusion that companies must incorporate gender equality into corporate strategy, ensuring that gender equality is integrated into the company's long-term strategic planning and vision of sustainable growth. Therefore, by adopting these recommendations, companies can create a lasting and positive impact on their employees, society and the achievement of SDG 5.0 by 2030